Methodological considerations regarding cognitive interventions in dementia - Ibañez, Agustin Mariano (2014)
Dementia causes massive cognitive, affective, and social impairment as well as concomitant functional decline. Cognitive interventions, together with pharmacological treatments, are acknowledged as important tools to delay mental weakening in dementing populations and to preserve the life quality of patients and their relatives (Prince et al., 2011; Woods et al., 2012). Given the socioeconomic impact of dementia on the health system, it is critical to assess cognitive intervention techniques in terms of cost-efficiency (Hurd et al., 2013). Nevertheless, most recent reports have neglected this issue, showing small, non-replicated, or even null results (Olazarán et al., 2010). Arguably, this is partly so because researchers are more specialized in the study of impairments than in the design of intervention programs. Consequently, there is no agreement on how to define cognitive intervention or how to measure its success (Giordano et al., 2010; Fernández-Prado et al., 2012).